Electromagnetic Instability in Plasma with Kappa Distribution Function in the Presence of Coulomb Collision - Fatemeh Nejadtaghi; Mohammad Mahdavi; Saeed Hassan pour; Hengameh Khanzadeh; Ali Tavassoli (Iranian Journal of Astronomy and Astrophysics)
In this research, an analytical expression of the Weibel electromagnetic instability growth rate is investigated for strongly coupled plasma in the presence of Coulomb collisions in the beam-plasma interaction under a low-frequency wave condition. In this regard, the distribution function governing the relativistic beam and plasma particles have been considered as semi-Maxwellian and Kappa distribution functions respectively. The effect of the temperature anisotropy parameter, the spectral index, quantum and relativistic parameters on Weibel electromagnetic instability growth rate have been investigated in collisional and non-collisional states. The obtained results show that the Coulomb collision frequency of particles plays an important role in suppressing the unstable modes in isotropic plasmas due to increase in the free energy of the plasma. Therefore, it was concluded that the Weibel instability growth rate in collision state has a more stable situation than in the non-collisional state in the strongly coupled plasma with Kappa distribution function.